KEMAMPUAN BERPIKIR FLEKSIBEL SISWA KELAS VIII PADA MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL DIKAJI BERDASARKAN HABITS OF MIND - Farid Fadhlurrahman; Sugiatno Sugiatno; Asep Nursangaji (Jurnal AlphaEuclidEdu, 2023)
Habits of mind is one of the many factors that influence flexible thinking skills. The purpose of this research is to describe students' flexible thinking skills on the materials system of linear equations in two variables reviewed based on habits of mind. The results obtained: There are 3 categories habits of mind that appear, which are 12,5% of high categories with flexibly thinking skills able to achieve the indicator of changing perspectives, able to achieve the indicator of considering options, and can able to achieve the indicator of producing alternatives, 75% of moderate categories with flexibly thinking skills less able to change perspective, less able to consider options, and able to generate alternatives, and 12,5% low of categories flexibly thinking skills less able to change perspective, less able to consider options, and less able to generate alternatives